2014
DOI: 10.3390/antibiotics3040632
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudes and Beliefs and Provider Practices Regarding Antibiotic Use for Acute Respiratory Tract Infections in Minya, Egypt

Abstract: The inappropriate use of antibiotics in the community is one of the major causes of antimicrobial resistance. This study aimed to explore the physician prescribing pattern of antibiotics for acute respiratory infections (ARIs) and to explore the knowledge, attitudes, and practices of patients regarding antibiotic use for ARIs. The study was conducted in Upper Egypt and used quantitative and qualitative research techniques. Eligible patients exiting outpatient clinics with ARIs were invited to participate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…This indicates the importance of establishing programs for the guidelines in increasing the adherence rate. In agreement with our results Bisno et al [12] emphasized that establishing of guidelines aims to assist the physicians to make decisions on treating specified conditions of URTI as pharyngitis in adult respiratory outpatient clinics.…”
Section: Adherence Rate In Each Type Of Urtissupporting
confidence: 81%
“…This indicates the importance of establishing programs for the guidelines in increasing the adherence rate. In agreement with our results Bisno et al [12] emphasized that establishing of guidelines aims to assist the physicians to make decisions on treating specified conditions of URTI as pharyngitis in adult respiratory outpatient clinics.…”
Section: Adherence Rate In Each Type Of Urtissupporting
confidence: 81%
“…The variation in the proportion may be explained by the fact that a package of oral antibiotics has, on average, 9.02 DDDs, while parenteral antibiotic packages have, on average, 0.72 DDDs. Some physicians and patients still believe that parenteral antibiotics are more effective than oral ones [ 42 , 43 ]. Ceftriaxone was the most dispensed parenteral antibiotic (34.27%), followed by ceftriaxone and sulbactam (31.32%).…”
Section: Discussionmentioning
confidence: 99%
“…This explanation is supported by two studies analyzing the rationale of antibiotic use in Egypt. The studies reported that beta lactam, macrolides, and cephalosporins antibiotics are the most common antibiotics prescribed for treating healthcare-associated infections in Egyptian hospitals [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%